Thyroid stimulating hormone directly modulates cardiac electrical activity. (December 2015) - Alonso, H.; Fernández-Ruocco, J.; Gallego, M.; Malagueta-Vieira, L.L.; Rodríguez-de-Yurre, A.; Medei, E.; Casis, O.
Abstract: Background: The electrocardiogram of hypothyroid patients shows a series of abnormalities of cardiac repolarization due to a reduction of some repolarizing K + currents and an increase of the L-type calcium current. Experimental and clinical works call into question the unique role of T3 and T4 in these mechanisms and correlate increased serum TSH levels with the repolarization abnormalities in patients with both subclinical and overt hypothyroidism. In this context, the aim of the present study was to investigate the direct effects of TSH upon cardiac electrical properties. Methods: The action potential recording and the ion channel subunits mRNA expression were obtained from left ventricle of adult rats. Additionally, the repolarizing K + currents and the L-type Ca 2+ current (ICa-L) were recorded in isolated rat adult ventricular myocytes by the patch-clamp technique. Results: 24 h exposure to TSH lengthened the action potential and slightly depolarized the resting membrane potential. TSH- receptor activation causes a reduction of the amplitude of Ito and IK1 currents caused by a reduction in channels expression. However, TSH had no effect on ICa -L, IK or IKur . Conclusion: These results support the idea that some of the electrical disturbances seen in hypothyroid hearts, such as the Ito and IK1 current reduction, could be caused not by low T3 but by the elevation of circulating TSH. Highlights: 24 h of TSH exposure significantly prolongs the cardiac action potential. TSH incubation decreases cardiac Ito and IK1 currents and mRNA expression, but does not modulate ICa-L. Acute (30 min) exposure to TSH does not modulate cardiac electrophysiological properties. Its direct effect on cardiac ionic channels supports a key role of TSH in the hypothyroidism-induced electrical disturbances.